CMOS-based bio-image sensor spatially resolves neural activity-dependent proton dynamics in the living brain - Horiuchi, Hiroshi; Agetsuma, Masakazu; Ishida, Junko; Nakamura, Yusuke; Lawrence Cheung, Dennis; Nanasaki, Shin; Kimura, Yasuyuki; Iwata, Tatsuya; Takahashi, Kazuhiro; Sawada, Kazuaki; Nabekura, Junichi (Nature communications, 2020)
Recent studies have shown that protons can function as neurotransmitters in cultured neurons. To further investigate regional and neural activity-dependent proton dynamics in the brain, the development of a device with both wide-area detectability and high spatial-ltemporal resolution is necessary. Therefore, we develop an image sensor with a high spatial-temporal resolution specifically designed for measuring protons in vivo. Here, we demonstrate that spatially deferent neural stimulation by visual stimulation induced distinct patterns of proton changes in the visual cortex. This result indicates that our biosensor can detect micrometer and millisecond scale changes of protons across a wide area. Our study demonstrates that a CMOS-based proton image sensor with high spatial and temporal precision can be used to detect pH changes associated with biological events. We believe that our sensor may have broad applicability in future biological studies. Protons have been discovered to play a role in neuronal signaling, but current methods to measure pH in the brain of animal models are limited. Here the authors develop a miniaturized proton image sensor that fits into a living mouse brain and can measure pH changes at micrometer and millisecond resolution scales.